Gallipoli - Moorehead, Alan, 1910-1983. (Ware : Wordsworth Editions, 1997)
"Using private papers as well as official records, Alan Moorehead re-creates with extraordinary vividness the drama of Gallipoli with its tragic hesitations and missed opportunities."--Page 4 of cover.
Includes bibliographical references and index.
Keywords: 1914-1918; World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula; Military campaigns; Turkey -- Gallipoli Peninsula